A Postmodernization of Customary International Law for the First World?. (13th November 2018) - d'Aspremont, Jean
Abstract : In his recent piece in the American Journal of International Law, B.S. Chimni depicts a doctrine of customary international law that has allowed the First World to impose its domination and promote its version of global capitalist justice. From Chimni's perspective, all the gimmicks and sophisticated dichotomies invented by international lawyers to refine international customary law serve a hegemonic socialization process whereby the center imposes its neoliberal ideals on an admiring periphery. But this diagnosis is certainly not the end of the story. In fact, Chimni's dismal image of the world and the role of custom therein is meant to foreground a more central project—i.e., the reinvention of customary international law around "the progressive ideas, beliefs, and practices of the global civil society" and geared towards the promotion of the "common good." My view is that Chimni's postmodernization of the doctrine of international customary law does not necessarily remedy the charges he levels against custom, let alone redefine the center and the periphery. As much as I share his diagnosis about custom's complicity in hegemonic socialization and the promotion of a global capitalist ethos, I contend that Chimni's postmodernization is at best unavailing and, at worse, rehabilitative of the First World's centrality in norm-setting. Instead of striving to reinvent the doctrine of custom, we must invest in strategies that draw on the malleability and fluidity of the current doctrine and facilitate the types of argumentation that "decenter" the First World, thereby directly empowering international lawyers elsewhere.